Optimization of electron bunch quality using a chirped laser pulse in laser wakefield acceleration - Arohi Jain; Devki Nandan Gupta (Physical Review Accelerators and Beams, 2021)
In this work, we perform particle-in-cell simulations to investigate the electron bunch quality using a chirped laser pulse in a laser wakefield acceleration mechanism. Particular attention is devoted to the electron beam quality improvement using a chirped laser pulse through group delay dispersion. By adjusting the value of group delay dispersion, the electron beam quality was controlled and improved in the range: charge (31–325 pC), energy (240–485 MeV), energy spread (2.1%–12.5%), and bunch duration (3.3–17 fs). The electron bunch charge highly depends on the chirping of the laser pulse. We anticipate that the ultrashort sub-GeV electron bunch generated in the laser wakefield acceleration mechanism using chirped laser pulses may be crucial in developing free-electron laser-based compact radiation sources.